Genetic Imaging of Neuroinflammation in Parkinson’s Disease: Recent Advancements - Yao, Longping; Wu, Jiayu; Koc, Sumeyye; Lu, Guohui (Frontiers in Cell and Developmental Biology, 2021)
Parkinson's disease (PD) is one of the most prevalent neurodegenerative aging disorders characterized by motor and non-motor symptoms due to the selective loss of midbrain dopaminergic (DA) neurons. The decreased viability of DA neurons slowly results in the appearance of motor symptoms such as rigidity, bradykinesia, resting tremor, and postural instability. These symptoms largely depend on DA nigrostriatal denervation. Pharmacological and surgical interventions are the main treatment for improving clinical symptoms, but it has not been possible to cure PD. Furthermore, the cause of neurodegeneration remains unclear. One of the possible neurodegeneration mechanisms is a chronic inflammation of the central nervous system, which is mediated by microglial cells. Impaired or dead DA neurons can directly lead to microglia activation, producing a large number of reactive oxygen species and pro-inflammatory cytokines. These cytotoxic factors contribute to the apoptosis and death of DA neurons, and the pathological process of neuroinflammation aggravates the primary morbid process and exacerbates ongoing neurodegeneration. Therefore, anti-inflammatory treatment exerts a robust neuroprotective effect in a mouse model of PD. Since discovering the first mutation in the α-synuclein gene (SNCA), which can cause disease-causing, PD has involved many genes and loci such as LRRK2, Parkin, SNCA, and PINK1. In this article, we summarize the critical descriptions of the genetic factors involved in PD's occurrence and development (such as LRRK2, SNCA, Parkin, PINK1, and inflammasome), and these factors play a crucial role in neuroinflammation. Regulation of these signaling pathways and molecular factors related to these genetic factors can vastly improve the neuroinflammation of PD.